Management of asymmetric development of enterprises in the digital economy - Kyryliuk, O. (Baltic International Academy, 2019)
Основною метою тез є дослідження особливостей управління асиметрією розвитку підприємства в контексті цифрової економіки. Досліджено сутність асиметрії розвитку підприємства в контексті цифрової економіки. Визначено характерні особливості інформаційних ресурсів в умовах сучасного динамічного середовища. Проаналізовано результати впровадження системи управління інформаційними ресурсами компанії. // The main purpose of the thesis is to study the features of managing the asymmetry of enterprise development in the context of the digital economy. The essence of asymmetry of enterprise development in the context of digital economy is investigated. The characteristic features of information resources in the modern dynamic environment are determined. The results of the implementation of the information resources management system of the company are analyzed.
Keywords: асиметрія розвитку підприємства; управління розвитком; ERP-система; інформаційні потоки; інформаційні ресурси; asymmetry of enterprise development; development management; ERP system; information flows; information resources